Computing with cells advances in membrane computing - Frisco, Pierluigi, 1970- (Oxford : Oxford University Press, 2009)
This monograph focuses on the theoretical computer science aspects of membrane computing and gives a comprehensive understanding of the computing power of the models considered.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Molecular computers; Cellular automata